HOW BODY LANGUAGE IS USED IN IMPROMPTU SPEAKING BY THIRD-YEAR STUDENTS IN THE FELTE, ULIS, VNU - Phạm, Thị Thanh Thủy (2020)
This research is aimed at investigating the awareness and habits of using body language by third-year students when they deliver impromptu speaking at the FELTE - VNU. By focusing on four common types of body language, the study makes suggestions on how to employ it to have an effective impromptu speaking in class. This research involved the participations of 3 lecturers and 25 students including the students of Fast-Track Program of the Division III, FELTE, ULIS, VNU. Both qualitative and quantitative methods were employed by using three kinds of data collection instruments: survey questionnaire, interview and observation.